Учебная социологическая литература: историографический анализ - Городяненко, В. (Социология: теория, методы, маркетинг, 1999)
There has been presented a review of the educational sociological literature published in 1980–1990th in Ukraine and other CIS countries that is used in Ukrainian Universities. The books have been appraised more due to the fact how they meet the requirements of educational practice than to their scientific contents. The reviewed books include textbooks, manuals, dictionaries, reference books, selections on social sciences.